Management Strategy of Small and Medium Enterprises during the Pandemic Covid-19 - Igor Turaev; Fozil Ganiev (Newinera Publisher, 2021)
This essay addresses the idea of small and medium-sized companies, the consequences of the pandemic on small and medium-sized enterprises, and approaches to creating and managing medium and small-sized businesses during the duration of the crisis. Most small and medium-sized businesses engage in formal commercial operations through cooperative enterprises. but there is a large effect on many who have medium-sized companies, delivery is impaired, as well as salespeople and those who depend on it; moreover, large numbers of salespeople would be hit by this pandemic. There is also an urgent need for increased management of small to mid-way and medium sized companies to be completed, which includes prioritizing the physical wellbeing of employees, leveraging digital marketing, and improving product and service efficiency, thus curtailing company revenue and costs, as well as re-evaluating the current strategy. As a result, that enables small and medium-sized businesses to stay afloat in the Covid-19pandemic.